EENet: Energy Efficient Neural Networks with Run-time Power Management - Li, Xiangjie; Shen, Yingtao; Zou, An; Ma, Yehan (2023 60th ACM/IEEE Design Automation Conference (DAC), 2023)
Deep learning approaches, such as convolution neural networks (CNNs), have achieved tremendous success in versatile applications. However, one of the challenges to deploy the deep learning models on resource-constrained systems is its huge energy cost. As a dynamic inference approach, early exit adds exiting layers to the networks, which can terminate the inference earlier with accurate results to save energy. The current passive decision-making for energy regulation of early exit cannot adapt to ongoing inference status, varying inference workloads, and timing constraints, let alone guide the reasonable configuration of the computing platforms alongside the inference proceeds for potential energy saving. In this paper, we propose an Energy Efficient Neural Networks (EENet), which introduces a plug-in module to the state-of-the-art networks by incorporating run-time power management. Within each inference, we establish prediction of where the network will exit and adjust computing configurations (i.e., frequency and voltage) accordingly over a small timescale. Considering multiple inferences over a large timescale, we provide frequency and voltage calibration advice, given inference workloads and timing constraints. Finally, the dynamic voltage and frequency scaling (DVFS) governor configures voltage and frequency to execute the network according to the prediction and calibration. Extensive experimental results demonstrate that EENet achieves up to 63.8% energy-saving compared with classic deep learning networks and 21.5% energy-saving compared with the early exit under state-of-the-art exiting strategies, together with improved timing performance.